Solution: Let x u ln = , dx
x
du
1
= , then
C
x
C
u
du u dx x
x
+
+
= +
+
= + = +
6
) ln 1 (
6
) 1 (
) 1 ( ) ln 1 (
1
6 6
5 5
Or,
+
+
= + = + C
x
x d x dx x
x 6
) ln 1 (
ln ) ln 1 ( ) ln 1 (
1
6
5 5
Example: Evaluate dx
x
x
+
4
1
Solution: Let
2
x u = , dx x du 2 = , then
C x C u du
u
dx
x
x
+ = + =
+
=
+
) ( tan
2
1
tan
2
1
1
1
2
1
1
2 1 1
2 4
Or, C x
x
x d
dx
x
x
+ =
+
=
+
) ( tan
2
1
) ( 1
) (
2
1
1
2 1
2 2
2
4
Example: Evaluate dx
e
x
1
1
2
Solution: Let
x
e u = , dx e du
x
= , then
C e C u du
u u
dx
e
x
x
+ = + =
) ( sec sec
1
1
1
1
1 1
2 2
2
u + 1
3
u
1
2
+ u u
2 3
u u +
2
u
u u
2
subtract
)
`
u
1 + u
subtract
)
`
1
subtract
)
`
Remainder
Example: Evaluate dx
e
x
+ 1
1
Solution: By letting
x
e u + =1 it will not give an appropriate form, why?
Instead rewrite the integrand as follows
1 1
1
+
=
+
x
x
x x
x
e
e
e e
e
, then
+
=
+
dx
e
e
dx
e
x
x
x
1 1
1
Now, let 1 + =
x
e u , dx e du
x
= , then
C e C u
u
du
dx
e
e
dx
e
x
x
x
x
+ + = + =
=
+
=
+
) 1 ln( ln
1 1
1
Example: Evaluate dx
x x
+
2 / 1 3 / 1
1
Solution: Let
6 / 1
x u = (where 6 is the smallest integer divisible by the denominator 2 and3). Then
dx x du
6 / 5
6
1
=
du u dx
5
6 =
du
u
u
u u
du u
u u
du u
dx
x x
+
=
+
=
+
=
+
1
6
) 1 (
6
) ( ) (
6
1
3
2
5
2 / 1 6 3 / 1 6
5
2 / 1 3 / 1
When the degree of the numerator is greater than the degree of the denominator, long
division is often helpful, i.e.
u
u u
u
u
+
+ =
+ 1
1
1
1
2
3
, then
dx
u
u u du
u
u
]
1
1
1 [ 6
1
6
2
3
+
+ =
+
C u u
u u
+
(
+ + = 1 ln
2 3
6
2 3
[ ] C x x x x + + + =
6 / 1 6 / 1 3 / 1 2 / 1
1 ln 6 6 3 2
3
Evaluating integrals having quadratic form in the form
+ + ) (
2
c bx ax
dx
and
+ + ) (
2
c bx ax
dx
using completing the square.
Example: Evaluate
+
2
6 5 x x
dx
Solution: Completing the square of ) 6 5 (
2
x x +
] 4 ) 3 [( ] 5 9 ) 3 [( ) 5 6 ( ) 6 5 (
2 2 2 2
= + = + = + x x x x x x

\

=
=
+
2 2 2
2
3
1
2
1
) 3 ( 4 6 5
x
dx
x
dx
x x
dx
Let
2
) 3 (
=
x
u , dx du
2
1
= , then
C
x
C u
u
du
x x
dx
+
= + =
=
+
)
2
3
( sin sin
1 6 5
1 1
2 2
Example: Evaluate
+ + 5 6 9
2
x x
dx
Solution: Completing the square of ) 5 6 9 (
2
+ + x x
]
9
4
)
3
1
[( 9 ]
9
5
9
1
)
3
1
[( 9 )
9
5
3
2
( 9 ) 5 6 9 (
2 2 2 2
+ + = + + = + + = + + x x x x x x
(
+
+
=
+ +
=
+ +
1
) 9 / 4 (
) 3 / 1 (
4
9
9
1
9
4
)
3
1
(
9
1
5 6 9
2
2
2
x
dx
x
dx
x x
dx
Let
) 3 / 2 (
) 3 / 1 ( +
=
x
u , dx du
2
3
= , then
C
x
C
x
C u
u
du
x x
dx
+

\

+
= +

\

+
= + =
+
=
+ +
2
1 3
tan
6
1
3 / 2
3 / 1
tan
6
1
tan
6
1
1
3
2
4
1
5 6 9
1 1 1
2 2
4
Evaluating integrals in the form dx
c bx ax
e dx
+ +
+
) (
) (
2
and dx
c bx ax
e dx
+ +
+
) (
) (
2
by letting the
numerator is the derivative of the function in the denominator or the function under the
square root. Then use completing the square as before.
Example: Evaluate dx
x x
x
+ +
+
5 6 9
3 2
2
Solution: Since 6 18 ) 5 6 9 (
2
+ = + + x x x
dx
d
, then, let the numerator becomes the derivative of the
denominator, i.e.
9
21
) 6 18 (
9
1
) 27 6 6 18 (
9
1
) 27 18 (
9
1
) 3 2 (
9
9
3 2 + + = + + = + = + = + x x x x x , then
+ +
+
+ +
+
=
+ +
+
5 6 9
9
21
5 6 9
6 18
9
1
5 6 9
3 2
2 2 2
x x
dx
dx
x x
x
dx
x x
x
The fist integration in the right hand side is in the form ) ( ln
) (
) (
x f dx
x f
x f
=
, then
5 6 9 ln
9
1
5 6 9
6 18
9
1
2
2
+ + =
+ +
+
x x dx
x x
x
The second integration in the right hand side can be obtained by completing the square as the
previous example, i.e.
)
2
1 3
( tan )
6
1
)(
9
21
(
5 6 9
9
21
1
2
+
=
+ +
x
x x
dx
.
Then
C
x
x x dx
x x
x
+
+
+ + + =
+ +
+
)
2
1 3
( tan )
6
1
)(
9
21
( 5 6 9 ln
9
1
5 6 9
3 2
1 2
2
5
Example: Evaluate dx
x x
x
+ +
+
5 6 9
3 2
2
Solution:
+ +
+
+ +
+
=
+ +
+
5 6 9
9
21
5 6 9
6 18
9
1
5 6 9
3 2
2 2
2
x x
dx
dx
x x
x
dx
x x
x
The fist integration in the right hand side is in the form ) ( 2
) (
) (
x f dx
x f
x f
=
, then
5 6 9 ) 2 )(
9
1
(
5 6 9
6 18
9
1
2
2
+ + =
+ +
+
x x dx
x x
x
The second integration can be obtained by completing the square as before
+

\

+
=
+ +
=
+ +
1
3 / 2
3 / 1
2
3
9
4
)
3
1
(
5 6 9
2
2
2
x
dx
x
dx
x x
dx
Let
) 3 / 2 (
) 3 / 1 ( +
=
x
u , dx du
2
3
= , then
+
= =
+
=
+ +
)
2
1 3
( sinh sinh
1 5 6 9
1 1
2 2
x
u
u
dx
x x
dx
Then
C
x
x x dx
x x
x
+
+
+ + + =
+ +
+
)
2
1 3
( sinh
9
21
5 6 9
9
2
5 6 9
3 2
1 2
2
6
62 Integration by Parts:
We have observed that every differentiation rule gives rise to corresponding integration rule.
So, let ) (x u and ) (x v are differentiable functions, then the product rule is:
dx
x du
x v
dx
x dv
x u x v x u
dx
d ) (
) (
) (
) ( )] ( ) ( [ + =
Integration both sides with respect to x of this equation gives us
dx
dx
x du
x v dx
dx
x dv
x u dx x v x u
dx
d ) (
) (
) (
) ( )] ( ) ( [
+ =
Since dx
dx
du
du = and dx
dx
dv
dv = then, after rearranging, we will have
) ( ) ( ) ( ) ( ) ( ) ( x du x v x v x u x dv x u
= == =
Which is called Integration by parts formula.
Then integration by parts formula is given by
This formula expresses one integral
dv u in terms of a second integral
du v which should be easier
than the first one.
Example: Evaluate
dx x ln
Solution: Let x u ln = and dx dv = , then
Differentiate Integrate
dx
x
du
1
= x v = , then
C x x x dx
x
x x x dx x + = =
ln
1
ln ln
= == = du v uv dv u
3 2 1
given
43 42 1
simpler
7
Example: Evaluate
dx x
1
sin
Solution: Let x u
1
sin
= and dx dv = , then
Differentiate Integrate
dx
x
du
2
1
1
= x v = , then
C x x x dx
x
x
x x dx
x
x
x x dx x + + =
+ =
=
2 1
2
1
2
1 1
1 sin
1
2
2
1
sin
1
sin sin
Example: Evaluate
dx x x sin
Solution: Let x u = and dx x dv sin = , then
Differentiate Integrate
dx du = x v cos = , then
C x x x dx x x x dx x x + + = =
sin cos cos cos sin
If we let x u sin = == = and dx x dv = == = , then
Differentiate Integrate
dx x du cos = == =
2
2
x
v = == = , then
== == == == dx x x x x dx x x cos
2
1
sin
2
1
sin
2 2
The new integration is worse than the integral we started with. So if the new integral is much more
complicated than the original one, go back and set u and dv equal to something else so that you end up
with an easier integral to solve.
8
Example: Evaluate
dx x x sin
2
Solution: Let
2
x u = and dx x dv sin =
Differentiate Integrate
dx x du 2 = x v cos = , then
+ = = xdx x x x dx x x x x dx x x cos 2 cos ) cos 2 ( ) cos ( sin
2 2 2
The integration in the right hand side
dx e x
x 2
Solution: Let
2
x u = and dx e dv
x
= , then
Differentiate Integrate
xdx du 2 =
x
e v = , then
= dx xe e x dx e x
x x x
2
2 2
The integration in the right hand side
dx xe
x
can be evaluated using again integration by parts by
letting:
x u = and dx e dv
x
= , then
Differentiate Integrate
dx du =
x
e v = , then
= =
x x x x x
e xe dx e xe dx xe , then
C e xe e x dx e x
x x x x
+ + =
2 2
2 2
Q. Prove the reduction formula
= dx e x n e x dx e x
x n x n x n 1
, for any positive n
9
Example: Evaluate
dx x e
x
3 sin
2
Solution: Let
x
e u
2
= and dx x dv 3 sin = , then
Differentiate Integrate
dx e du
x 2
2 = x v 3 cos
3
1
= , then
= dx x e x e dx x e
x x x
3 cos )
3
2
( 3 cos
3
1
3 sin
2 2 2
Integration by parts again for the integration in the right hand side of the last equation, we have
Let
x
e u
2
= and dx x dv 3 cos = , then
Differentiate Integrate
dx e du
x 2
2 = x v 3 sin
3
1
= , then
+
= ] 3 sin
3
2
3 sin
3
1
[
3
2
3 cos
3
1
3 sin
2 2 2 2
xdx e x e x e dx x e
x x x x
Observe that the last integral is the integral that we started with. If the original integral is I then
I x e x e I
x x
9
4
3 sin
9
2
3 cos
3
1
2 2
+
=
C x e x e I
x x
+ +
= + 3 sin
9
2
3 cos
3
1
)
9
4
1 (
2 2
Then
C x e x e C x e x e I
x x x x
+ + = + +
= 3 sin
13
2
3 cos
13
3
] 3 sin
9
2
3 cos
3
1
[
13
9
2 2 2 2
10
Note that: The integration by parts can be applied for definite integrals as
Example: Evaluate
2
1
3
ln dx x x
Solution: let x u ln = and dx x dv
3
=
Differentiate Integrate
dx
x
du
1
=
4
4
1
x v = , then
[ ] [ ]
2
1
4 4 4
2
1
4
2
1
4
2
1
3
16
1
1 ln ) 1 ( 2 ln ) 2 (
4
1 1
)
4
1
( ln
4
1
ln x dx
x
x x x dx x x =
(
=
[ ] [ ]
16
15
2 ln
4
16
) 1 ( ) 2 (
16
1
0 2 ln ) 2 (
4
1
4 4 4
= =
16
15
2 ln 2 =
[ ]
=
b
a
b
a
b
a
du v uv dv u
11
63 Trigonometric Techniques of Integration:
Integration of trigonometric function
C x dx x + =
cos sin
C x dx x + =
sin cos
C x C x dx
x
x
dx x + = + = =
sec ln cos ln
cos
sin
tan
C x dx
x
x
dx x + = =
sin ln
sin
cos
cot
C x x dx
x x
x x x
dx
x x
x x
x dx x + + =
+
+
=
+
+
=
tan sec ln
tan sec
tan sec sec
tan sec
tan sec
sec sec
2
C x x dx
x x
x x x
dx
x x
x x
x dx x + + =
+
+
=
+
+
=
cot csc ln
cot csc
cot csc csc
cot csc
cot csc
csc csc
2
Integration of squaring the trigonometric functions:
To evaluate these integrals, we need identities
1 cos sin
2 2
= + x x , x x
2 2
sec 1 tan = + , x x
2 2
csc cot 1 = +
2
2 cos 1
sin
2
x
x
= ,
2
2 cos 1
cos
2
x
x
+
=
C
x
x dx x dx x + = =
]
2
2 sin
[
2
1
) 2 cos 1 (
2
1
sin
2
C
x
x dx x dx x + + = + =
]
2
2 sin
[
2
1
) 2 cos 1 (
2
1
cos
2
C x x dx x dx x + = =
tan ) 1 (sec tan
2 2
C x x dx x dx x + = =
cot ) 1 (csc cot
2 2
C x dx x + =
tan sec
2
C x dx x + =
cot csc
2
12
Integration in the form
dx x x
n m
cos sin
a If m or n is an odd positive integer
Isolate one factor of the odd number and then use the identity 1 cos sin
2 2
= + x x
Example: Evaluate
dx x x
4 3
cos sin
Solution: ) (cos cos ) cos 1 ( sin cos sin cos sin
4 2 4 2 4 3
= = x d x x dx x x x dx x x
C
x x
x d x x + = =
)
7
cos
5
cos
( ) (cos ) cos (cos
7 5
6 4
Example: Evaluate
dx x x
5
cos sin
Solution: ) (sin ) sin 1 ( sin cos cos sin cos sin
2 2 4 5
x d x x dx x x x dx x x
= =
+ = + = ) (sin ) sin sin 2 (sin ) (sin ) sin sin 2 1 ( sin
2 / 9 2 / 5 2 / 1 4 2
x d x x x x d x x x
C x x x + + =
2 / 11 2 / 7 2 / 3
sin
11
2
sin
7
4
sin
3
2
b If m and n are both even positive integer
Use the halfangle formula
2
2 cos 1
sin
2
x
x
= ,
2
2 cos 1
cos
2
x
x
+
= to reduce the powers
in the integrand.
Example: Evaluate
dx x
4
cos
Solution:
+ + =

\
 +
= = dx x x dx
x
dx x dx x ) 2 cos 2 cos 2 1 (
4
1
2
2 cos 1
) (cos cos
2
2
2 2 4
C
x
x
x
x dx x x + + + + = + + + =
)]
4
4 sin
(
2
1
2
2 sin
2 [
4
1
)] 4 cos 1 (
2
1
2 cos 2 1 [
4
1
C x x x + + + = 4 sin
32
1
2 sin
4
1
8
3
Example: Evaluate
dx x x
2 2
sin cos
Solution: dx x dx
x x
dx x x ) 2 cos 1 (
4
1
2
2 cos 1
2
2 cos 1
sin cos
2 2 2
=

\


\
 +
=
C
x
x C
x
x x dx x +
(
= +
(
+ = + =
4
4 sin
8
1
)
4
4 sin
(
2
1
4
1
] ) 4 cos 1 (
2
1
1 [
4
1
13
Integration in the form
dx x x
n m
sec tan
a If m is an odd positive integer
Isolate one factor of ( x x tan sec ) and then replace any ( x
2
tan ) by the identity
1 sec tan
2 2
= x x
Example: Evaluate
dx x x
3 3
sec tan
Solution:
= = ) (sec sec tan ) tan (sec sec tan sec tan
2 2 2 2 3 3
x d x x dx x x x x dx x x
C
x x
x d x x x d x x + = = =
3
sec
5
sec
) (sec ) sec (sec ) (sec sec ) 1 (sec
3 5
2 4 2 2
b If n is an even positive integer
Isolate one factor of ( x
2
sec ) and then replace any ( x
2
sec ) by the identity
1 tan sec
2 2
+ = x x
Example: Evaluate
dx x x
4 2
sec tan
Solution:
+ = = ) (tan ) 1 (tan tan ) (sec sec tan sec tan
2 2 2 2 2 4 2
x d x x dx x x x dx x x
C
x x
x d x x + + = + =
3
tan
5
tan
) (tan ) tan tan
3 5
2 4
c If m is an even positive integer and n is an odd integer
Replace any factors of ( x
2
tan ) with ( 1 sec
2
x ) and then use the reduction formula for
= xdx
n
n
x
n
dx x
n n n 2 2
sec
1
2
tan sec
1
1
sec
Example: Evaluate
dx x x
3 2
sec tan
Solution: dx x x dx x x dx x x
= = ) sec (sec sec ) 1 (sec sec tan
3 5 3 2 3 2
= xdx x x dx x
3 3 5
sec
1 5
2 5
tan sec
1 5
1
sec Q
= + = xdx x x dx x xdx x x dx x x
3 3 3 3 3 3 2
sec
4
1
tan sec
4
1
sec sec
4
3
tan sec
4
1
sec tan
(
xdx x x x x sec
2
1
tan sec
1 3
1
4
1
tan sec
4
1
3
[ ] C x x x x x x + + + = tan sec ln tan sec
8
1
tan sec
4
1
3
14
x
2
2
4 x
The proof of the previous reduction formula suing integration by parts:
Let
2
sec
=
n
u and xdx dv
2
sec =
Differentiate Integrate
xdx x x n du
n
tan sec sec ) 2 (
3
= x v tan = , then
dx x x n x x dx x
n
n n
2
2 2
sec tan ) 2 ( tan sec sec
=
dx x x n x x
n
n
2
2 2
sec ) 1 (sec ) 2 ( tan sec
=
dx x x n x x
n n n
= ) sec (sec ) 2 ( tan sec
2 2
dx x n x x dx x n
n n n
+ =
2 2
sec ) 2 ( tan sec sec ) 1 (
dx x
n
n
x x
n
dx x
n n n
=
2 2
sec
1
) 2 (
tan sec
1
1
sec
Trigonometric substitution
This method is effective if the integrands contain a term in the form
2 2
x a ,
2 2
x a + ,
2 2
a x , for 0 > a
a) The integrand contains a term in the form
2 2
x a
We can eliminate the square root by
Let sin a x = , for
2 2
cos sin 1 sin
2 2 2 2 2 2
a a a a x a = = =
Since 0 cos , for
2 2
Example: Evaluate dx
x x
2 2
4
1
Solution: Let sin 2 = x for
2 2
, then d dx cos 2 =
d d dx
x x
) cos 2 (
cos 2
1
sin 4
1
) cos 2 (
sin 4 4 sin 4
1
4
1
2
2 2 2 2
=
C
x
x
C d d +
= + = = =
2
2
2
4
4
1
cot
4
1
csc
4
1
sin 4
1
Q. Prove that C x a
a
x
a
x a
dx x a +
(
+ =
2 2
2
1
2
2 2
sin
2
15
x
2
9 x +
3
b) The integrand contains a term in the form
2 2
x a +
We can eliminate the square root by
Let tan a x = , for
2 2
< <
sec tan 1 tan
2 2 2 2 2 2
a a a a x a = + = + = +
Since 0 sec , for
2 2
< <
Example: Evaluate dx
x
+
2
9
1
Solution: Let tan 3 = x , for
2 2
d d dx
x
) sec 3 (
sec 3
1
) sec 3 (
tan 9 9
1
9
1
2 2
2 2
=
+
=
+
C
x x
C d + +
+
= + + = =
3 3
9
ln tan sec ln sec
2
Q. Prove that C
a
x
a
x a a
x a
x
dx x a +
(
(
+
+
+ + = +
2 2 2
2 2 2 2
ln
2 2
c) The integrand contains a term in the form
2 2
a x
We can eliminate the square root by
Let sec a x = , for )]
2
( or )
2
0 [
< <
tan tan sec
2 2 2 2 2 2
a a a a a x = = =
Since tan is positive and negative, for ]
2
( or )
2
0 [
< <
16
x
25
2
x
5
Example: Evaluate dx
x
x
25
2
Solution : Let sec 5 = x , for )
2
0 [
< , where we chose the first half of the domain, then
d dx tan sec 5 =
d dx
x
x
) tan sec 5 (
sec 5
25 sec 25 25
2 2
=
+ = = = C d d ] [tan 5 ) 1 (sec 5 tan 5
2 2
C
x x
+
(
(
=
5
sec
5
25
5
1
2
Q. Prove that C
a
x
a
a x a
a x
x
dx a x +
(
(
2 2 2
2 2 2 2
ln
2 2
17
64 Integration of Rational Functions Using Partial Fractions:
The rational function
) (
) (
) (
x g
x h
x f = , where ) (x h , ) (x g are polynomials, can be decomposed into a sum
of simpler terms by the method called Partial Fractions as follows:
If ) (x f is proper, that is the deg( ) (x h ) < deg( ) (x g ), then ) (x f can be expressed as a sum
of simpler fractions.
If ) (x f is improper, that is the deg( ) (x h ) > deg( ) (x g ), then we must apply first long
division until the remainder ) (x R is obtained such that deg( ) (x R ) < deg( ) (x g ), i.e. ) (x f
will be in the form
) (
) (
) ( ) (
x g
x R
x p x f + =
Factors the denominator ) (x g as a product of linear factors ) ( b ax + and irreducible
quadratic factors (quadratic factors that have no real factorization) ) (
2
c bx ax + + .
Express the proper rational function
) (
) (
x g
x R
as sums of partial fractions.
Case I: Linear factors
If ) (x g has linear factors in the form ) ( b ax + , then
) ( ) ( ) ( ) ( ) )( (
) (
) (
2 2
2
1 1
1
2 2 1 1 n n
n
n n
b x a
c
b x a
c
b x a
c
b x a b x a b x a
x R
x f
+
+ +
+
+
+
=
+ + +
= L
L
Example: Evaluate dx
x x
x x
3
2
2 7 3
Solution: Rewrite the integrand using partial fractions
) 1 ( ) 1 ( ) 1 )( 1 (
2 7 3 2 7 3
2
3
2
+
+
+ =
+
=
x
C
x
B
x
A
x x x
x x
x x
x x
Multiply both sides by the denominator ) 1 )( 1 ( + x x x , we get
) 1 )( ( ) 1 )( ( ) 1 )( 1 ( 2 7 3
2
+ + + + = x x C x x B x x A x x
18
subtract
x x x
x x x
16 4 2
5 15 4 2
2 3
2 3
+
)
`
8 2
2
x x
x 2
5 + + x
) (x R
8 2
5
2
8 2
5 15 4 2
2 2
2 3
+
+ =
+
x x
x
x
x x
x x x
Since the two sides are identical for all x , then by taking 0 = x , 1 = x , and 1 = x which will
make two terms of the right side zero ,we get
Taking 0 = x ) 1 )( 1 ( 2 = A 2 = A
Taking 1 = x ) 2 )( 1 ( 6 B = 3 = B
Taking 1 = x ) 2 )( 1 ( 8 = C 4 = C
Then c x x x dx
x x x
dx
x x
x x
+ + + =
(
+
+
1 ln 4 1 ln 3 ln 2
) 1 (
4
) 1 (
3 2 2 7 3
3
2
Example: Evaluate dx
x x
x x x
+
8 2
5 15 4 2
2
2 3
Solution: Since the degree of the numerator is greater than the degree of the denominator, then
we need long division
) 2 )( 4 (
5
2
+
+
+ =
x x
x
x
Then the proper function can be expressed as
2 4 ) 2 )( 4 (
5
+
+
=
+
+
x
B
x
A
x x
x
Multiply both sides by the denominator ) 2 )( 4 ( + x x , we get
) 4 ( ) 2 ( 5 + + = + x B x A x
The two sides are identical for all x , then
Taking 2 = x ) 6 ( 3 = B
2
1
= B
Taking 4 = x ) 6 ( 9 A =
2
3
= A
dx
x x
x dx
x x
x x x
(
\

+
\

+ =
+
2
1
2
1
4
1
2
3
2
8 2
5 15 4 2
2
2 3
c x x x + + + = 2 ln
2
1
4 ln
2
3
2
19
Case II: Repeated linear factors
If ) (x g has repeated linear factors in the form
n
b ax ) ( + , then
L L L
L L
+
+
+ +
+
+
+
+ =
+
=
n
n
n
b ax
c
b ax
c
b ax
c
b ax
x R
x f
) ( ) (
) (
) (
) (
) (
2
2 1
Example: Evaluate dx
x x x
x x
+ +
+ +
2 3
2
2
6 20 5
Solution: Rewrite the integrand using partial fractions
2 2
2
2 3
2
) 1 (
) 1 (
) 1 (
6 20 5
2
6 20 5
+
+
+
+ =
+
+ +
=
+ +
+ +
x
C
x
B
x
A
x x
x x
x x x
x x
Multiply both sides by the denominator
2
) 1 ( + x x , we get
) ( ) 1 )( ( ) 1 ( 6 20 5
2 2
x C x x B x A x x + + + + = + +
The two sides are identical for all x , then
Taking 0 = x
2
) 1 ( 6 A = 6 = A
Taking 1 = x ) 1 ( 6 20 5 = + C 9 = C
To find B, Substitute any convenient value for x , as 1 = x
) 1 ( 9 ) 2 )( 1 ( ) 2 ( 6 6 20 5
2
+ + = + + B 1 = B
Then dx
x
x x
dx
x x x
x x
(
+
+
+
=
+ +
+ +
2 2 3
2
) 1 (
9
) 1 (
1 6
2
6 20 5
c x x x + + + =
1
) 1 ( 9 1 ln ln 6
Case III: Irreducible quadratic form:
If ) (x g has irreducible quadratic factors in the form ) (
2
c bx ax + + , then
L L
L L
+
+ +
+
+ =
+ +
=
) ( ) (
) (
) (
2 2
c bx ax
B Ax
c bx ax
x R
x f
20
Example: Evaluate dx
x x x
x x
+ + +
+ +
) 5 2 )( 2 (
2 6 5
2
2
Solution: Rewrite the integrand using partial fractions
) 5 2 (
) 2 (
) 5 2 )( 2 (
2 6 5
2 2
2
+ +
+
+
+
=
+ + +
+ +
x x
C Bx
x
A
x x x
x x
Multiply both sides by the denominator ) 5 2 )( 2 (
2
+ + + x x x , we get
) 2 )( ( ) 5 2 ( 2 6 5
2 2
+ + + + + = + + x C Bx x x A x x
Taking 2 = x ) 5 4 4 ( 2 12 20 + = + A 2 = A
Matching up the coefficients of like powers of x , w get
Coefficient of
1
x C B A + + = 2 2 6 C B + = 2 2 (1)
Coefficient of
0
x C A 2 5 2 + = (2)
Solving (1) and (2) we get 3 = B , 4 = C , then
dx
x x
x
x
dx
x x x
x x
(
+ +
+
+
=
+ + +
+ +
5 2
4 3
2
2
) 5 2 )( 2 (
2 6 5
2 2
2
dx
x x
x
x dx
x x x
x x
(
+ +
+ + =
+ + +
+ +
5 2
4 3
2 ln 2
) 5 2 )( 2 (
2 6 5
2 2
2
Let dx
x x
x
I
(
+ +
=
5 2
4 3
2
, making the nominator is the derivative of the denominator
) 2 2 ( + x , i.e.
7 ) 2 2 (
2
3
)
3
14
2 2 (
2
3
)
3
8
2 2 2 (
2
3
)
3
8
2 (
2
3
)
3
4
( 3 4 3 + = + = + = = = x x x x x x
Then dx
x x
x x dx
x x
dx
x x
x
I
+ +
+ + =
+ +
+
+ +
=
5 2
7
5 2 ln
2
3
5 2
7
5 2
2 2
2
3
2
2
2 2
The last integral can be obtained using completing the square, i.e

\

+
=
+ +
=
+ +
2
1
tan
2
7
4 ) 1 (
7
5 2
7
1
2 2
x
dx
x
dx
x x
Then c
x
x x x dx
x x x
x x
+

\

+
+ + + + + =
+ + +
+ +
2
1
tan
2
7
) 5 2 ( ln
2
3
2 ln 2
) 5 2 )( 2 (
2 6 5
1 2
2
2
21
Case III: Repeated irreducible quadratic form:
If ) (x g has repeated irreducible quadratic factors in the form
n
c bx ax ) (
2
+ + , then
L L L
L L
+
+ +
+
+ +
+ +
+
+
+ +
+
+ =
+ +
=
n
n n
n
c bx ax
B x A
c bx ax
B x A
c bx ax
B x A
c bx ax
x R
x f
) ( ) ( ) ( ) (
) (
) (
2 2 2
2 2
2
1 1
2
Example: Evaluate dx
x x
x x x
+
2 2
3 2
) 1 (
2 1
Solution: Rewrite the integrand using partial fractions
2 2
2 2
2
1 1
2 2
3 2
) 1 ( ) 1 ( ) 1 (
2 1
+
+
+
+
+
+ =
+
x
C x B
x
C x B
x
A
x x
x x x
Multiply both sides by the denominator
2 2
) 1 ( + x x , we get
) )( ( ) 1 )( )( ( ) 1 ( 2 1
2 2
2
1 1
2 2 3 2
x C x B x x C x B x A x x x + + + + + + =
Matching up the coefficients of like powers of x , w get
1 = A , 1
1
= B , 1
1
= C , 1
2
= B , 0
2
= C , then
dx
x
x
x
x
x
dx
x x
x x x
(
+
+
+
+
=
+
2 2 2 2 2
3 2
) 1 ( ) 1 (
1 1
) 1 (
2 1
+
+
+
+
=
2 2
2
2 2
) 1 (
2
1
) 1 (
1
) 1 (
2
2
1 1
x
dx
dx
x
dx
x
x
dx
x
c x x x x + + + + =
1 2 1 2
) 1 (
2
1
tan 1 ln
2
1
ln
22
65 Integration Using tables and Computer Algebra Systems (CAS)
Using Table of Integrals
An extensive tables of indefinite and definite integrals are published in standarad reference
books such as Standard Mathematical tables and Formula edited by William H. Beyer and
Table of integrals, Series and Products compile by Gradshteyn and Ryzhik.
To use the table you must first rewrite the integral using substitution or algebraic manipulation to
transform the given integral into one of the forms in the table.
Using a Computer Algebra Systems: (CAS)
Some calculators like TI89 and HP48 and systems such as Mathematica , Maple, and Derive
which can run on any personal computer, have integral formulas stored internally and can
perform substitution that transform a given integral into that occurs in its stored formulas.
Although CAS can match patterns with tables of integrals stored in computer memory, the
hand manual calculation should be learned because it may yield a simpler answer than a
computer result and to catch sometimes the incorrect results.
23
y
0
y
0
66 Improper Integrals:
So far in the study of the definite integral
b
a
dx x f ) ( we have dealt with a function f that was
always defined on a finite interval ] , [ b a and does not have infinite discontinuity. In this section we
introduce the concepts of the definite integral to the following cases:
1 where ) (x f has an infinite discontinuity in ] , [ b a .
2 where the interval of integration is infinite.
In either case the integral is called improper integral.
Case I: Improper Integrals with Discontinuous Integrands:
Definition:
Consider the improper integral
b
a
dx x f ) (
1) If ) (x f is continuous function on the interval ) , [ b a and discontinuous at b such that
=
) ( lim x f
b x
, then
=
t
a
b t
b
a
dx x f dx x f ) ( lim ) (
2) If ) (x f is continuous function on the interval ] , ( b a and discontinuous at a such that
=
+
) ( lim x f
a x
, then
+
=
b
t
a t
b
a
dx x f dx x f ) ( lim ) (
24
y
0
3) If ) (x f is continuous function on the interval ] , [ b a except it has discontinuity at a point
] , [ b a c such that =
) ( lim x f
c x
, then
+
+ =
b
s
c s
t
a
c t
b
a
dx x f dx x f dx x f ) ( lim ) ( lim ) (
The improper integral
b
a
dx x f ) ( is called convergent if the corresponding limit exists and
divergent if the limit does not exist.
Example: Determine whether the improper integral
1
0
1
dx
x
converges or diverges.
Solution: Note that =
+
x
x
1
lim
0
, then
[ ] [ ] 2 2 2 lim 2 lim
1
lim
1
0
1
0
1
0
1
0
= = = =
+ + +
t x dx
x
dx
x t
t
t
t
t
, converges.
Example: Determine whether the improper integral
2
1
2
) 2 (
1
dx
x
converges or diverges.
Solution: Note that =
2
2
) 2 (
1
lim
x
x
, then
[ ] =
(
= =
2 1
1
2
1
lim ) 2 ( lim
) 2 (
1
lim
) 2 (
1
2
1
1
2
1
2
2
2
1
2
t
x dx
x
dx
x
t
t
t
t
t
, diverges.
25
Example: Determine whether the improper integral
3
0
3
1
1
dx
x
converges or diverges
Solution: Not that at 1 = x which is in the interval ] 3 , 0 [ , =
3
1 1
1
lim
x x
and + =
3
1 1
1
lim
x x
,
then
dx
x
dx
x
dx
x
s
s
t
t
+
+
3
3
1
0
3
1
3
0
3
1
1
lim
1
1
lim
1
1
[ ] [ ]
2
3
1 0
2
3
) 1 ( ) 1 (
2
3
lim ) 1 (
2
3
lim
1
1
lim
3 / 2 3 / 2
1
0
3 / 2
1
0
3
1
= = =
(
t x dx
x t
t
t
t
t
[ ] [ ]
3 3 / 2 3 / 2 3 / 2
1
3
3 / 2
1
3
3
1
4
2
3
0 ) 2 (
2
3
) 1 ( ) 1 3 (
2
3
lim ) 1 (
2
3
lim
1
1
lim = = =
(
+ + +
s x dx
x s
s
s
s
s
Then [ ] 1 4
2
3
4
2
3
2
3
1
1
3 3
3
0
3
= + =
dx
x
, converges.
Case II: Improper integrals with an infinite limit of integration:
Definition:
Consider the improper integral
b
a
dx x f ) (
1) If ) (x f is continuous function on the interval ) , [ a , then
=
t
a
t
a
dx x f dx x f ) ( lim ) (
2) If ) (x f is continuous function on the interval ] , ( b , then
=
b
t
t
b
dx x f dx x f ) ( lim ) (
3) If ) (x f is continuous function on the interval ) , ( , then
+ =
s
a
s
a
t
t
dx x f dx x f dx x f ) ( lim ) ( lim ) ( for any convenient choice of a .
26
The improper integral
b
a
dx x f ) ( is called convergent if the corresponding limit exists and divergent if
the limit does not exis
Example: Determine whether the improper integral
1
1
dx
x
converges or diverges.
Solution:
[ ] [ ] = = = =
t t dx
x
dx
x
t
t
t
t
t
ln 1 ln lim ln lim
1
lim
1 1
1 1
, diverges.
Example: Determine whether the improper integral
1
2
1
dx
x
converges or diverges.
Solution:
1 1
1
lim
1
lim
1
lim
1
1 1
2
1
2
=
(
=
(
= =
t x
dx
x
dx
x
t
t
t
t
t
, converges.
Example: Determine whether the improper integral
0
1
1
dx
x
converges or diverges.
Solution:
[ ] [ ] = = =
t x dx
x
dx
x
t
t
t
t
t
1 2 2 lim 1 2 lim
1
1
lim
1
1 0
0 0
, diverges.
Example: Determine whether the improper integral
dx xe
x
2
converges or diverges.
Solution: The choice 0 = a , then
+ =
0
0
2 2 2
dx xe dx xe dx xe
x x x
+ =
s
x
s
t
x
t
x
dx xe dx xe dx xe
0
0
2 2 2
lim lim
[ ] [ ]
s
x
s
t
x
t
s
x
s
t
x
t
x
e e dx e dx e dx xe
0
0
0
2
0
2
2 2 2 2 2
lim
2
1
lim
2
1
2
1
lim
2
1
lim
+ = + =
[ ] [ ] 0
2
1
2
1
1 lim
2
1
1 lim
2
1
2 2
= + = =
s
s
t
t
e e , converges
27
Example: Determine whether the improper integral
1
0
ln dx x x converges or diverges.
Solution: ( )
(
(
= = =
+ + +
1
2
1
2
0
1
2
0
1
0
1
0
1
ln lim
2
1
ln lim
2
1
ln lim ln
t
t
t
t
t
t
t
dx
x
x x x dx x dx x x dx x x
( ) ( )
(
(


\

=
(
(


\

=
+ +
2 2
1
ln 0 lim
2
1
2
ln lim
2
1
2
2
0
1
2
1
2
0
t
t t
x
x x
t
t
t
t
4
1
2
1
0
2
1
2 2
1
) / 1 (
ln
0 lim
2
1
2
2
0
=
(
=
(
(


\



\

=
+
t
t
t
t
, converges, using L'Hopital's Rule